(Re) Defining Emerging Risks. Issue 11 (17th January 2017) - Mazri, Chabane
Abstract: The concept of emergence in risk management can be seen as a revealing symptom of the increasing need for organizations to update their portfolio of risks and opportunities in a rapidly changing and highly competitive environment. Accordingly, the concept of emerging risks has been widely discussed in both scientific and business communities, with, however, a lack of agreement as to whether we should distinguish these risks from others and, if so, what should be the adopted approach for their governance. After reviewing a large set of definitions and conceptions of emerging risks, this article aims at exploring the existence of distinctive features allowing the characterization of a risk as emerging or not. First, we will demonstrate that the features used in the various definitions are ineffective to achieve this distinction. Furthermore, we will argue that all events and consequences associated with risks are or have been states of nature that emerged from complex interactions involving combinations of hazardous activities and stakes. Accordingly, emerging risks are no longer a specific category of risks; they are rather an early step in every risk life cycle that deserves specific governance approaches.